Technological tools usable for the observation of the high level sport in the structures of training - Calmet, M.; Ahmaidi, S. (Expertise in Elite sport. 2nd International Days of Sport Sciences, 12.-15. November 2002, INSEP, Paris (France), 2002)
Introduction Technological tools allowing an accurate observation of sport gesture are still very often out of reach financially, materially or difficult to operate for the non-specialist in these technologies. Hypotheses Computers, their peripherals, notably the video acquisition cards, the means of storage, and the current software packages (spreadsheets and tools of presentation assisted by computer) would allow making tools of observation simpler to operate as they are now commonly used.